Counseling and social work - Brearley, Judith (Buckingham : Open University Press, 1995)
This book is about: The development of counselling in social work; The context of counselling in social work; The practice of counselling in social work; ...
Keywords: Social service; Psychological aspects; Counselling; Social service; Social service -- Psychological aspects; Counseling